2018
DOI: 10.1002/mar.21154
|View full text |Cite
|
Sign up to set email alerts
|

“Retail is detail! Give consumers a gift rather than a bundle”: Promotion framing and consumer product returns

Abstract: Retailers often use the promotion strategy of offering supplementary products (e.g., free gift, bundle) to attract consumers and increase sales. Despite the growing literature on the promotions that are differently framed but offer economically identical values, little research has examined the link between promotion framing and consumer product returns. The current article sheds light on this relationship, hypothesizing that a free gift promotion would be superior to a bundle promotion in reducing consumer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
(81 reference statements)
0
25
0
Order By: Relevance
“…When an existing luxury brand launches a new product, they have a high probability of using LQS and LTS messages (Wiedmann et al, 2009). LQS messages allow consumers to assume that the goods are scarce and prestigious, thus affecting consumers' desire to gain the product (Lee and Yi, 2019). LTS messages are adopted in the launch period of the product lifecycle, especially for luxury products (Wu and Lee, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…When an existing luxury brand launches a new product, they have a high probability of using LQS and LTS messages (Wiedmann et al, 2009). LQS messages allow consumers to assume that the goods are scarce and prestigious, thus affecting consumers' desire to gain the product (Lee and Yi, 2019). LTS messages are adopted in the launch period of the product lifecycle, especially for luxury products (Wu and Lee, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although research on how to give is sparse, the extant research (just discussed) clearly shows that the aspects comprising how to give are important, as they can influence recipients' reactions to gifts. Indeed, outside the realm of gift-giving, much research spanning multiple areas of psychology (e.g., persuasion, judgement and decision making) indicates that how products are framed, received, and perceived is, arguably, about as important to consumers as the products themselves (e.g., Lee & Yi, 2019;Schmidt & Maier, 2019).…”
Section: Gift-giving Decisionsmentioning
confidence: 99%
“…and the mechanism of persuasion (Campbell & Kirmani, 2008). For instance, Lee and Yi (2019) found that consumers' belief regarding promotion framing (gift-framed vs. bundle-framed) served as persuasion knowledge that affected how people decided to return a product. Consumers tend to perceive more loss from giving up giftframed (vs. bundle framed) promotions, leading to a lower return rate for gift-framed package.…”
Section: Theoretical Implicationsmentioning
confidence: 99%